Correlation and Partitioning of Some Heavy Metals in Aquatic Media Around a Make Shift Crude Oil Refining Area - Ibigoni Clinton, Howard; Iyabode Khadijat, Abiodun (International Journal of Environment, 2019)
The major aim of the present study was to evaluate the concentration levels of some heavy metals and their relationships between the bottom sediments, its overlaying (bottom) water and the surface water of the study area in Andoni local Government of Rivers State, Nigeria (Long.7° 20’ 48.639’’E and Lat.4 29 20.169N) using standard methods of analysis. The mean result showed variation patterns (P<0.05) of the metals in each of the medium as - surface water – Mg>N=Cu=Zn>Pb=Cd>V; bottom water – Mg>Cu>Ni=Zn>Pb=Cd>V and bottom sediments – Mg=Zn>Pb>Cd>Cu=Ni>V, while that of the media for each metal is Sediment >> Bottom water=Surface water. The sediments of the study area had more positive significant correlations among metal pairs than others indicating that metals were more bound to the sediments than in the water columns. V-Cd, V-Pb and V-Ni showed significant positive correlations in the water columns indicating that their input sources may likely be the same, which could have been from petroleum related activities. The level of contamination of the study area is relatively high when compared to related studies within and outside the region. It is therefore recommended that the activities of this make-shift refining of crude oil in the area should be stopped by the relevant regulatory agencies and also further studies on other media should be carried out.